(untitled) (Journal of Social Sciences Review, 2023)
Translation is more than just converting text between two languages; it also involves two very different cultures. During translation, translators encounter elements that are specific to the languages they are working with, which are called Culture-Specific Items (CSIs). Translation theorists create a variety of translation techniques to effectively deal with CSIs. In this respect, the theory of Venuti (2008) regarding the techniques of foreignization and domestication is very helpful. This article aims to examine the use of these techniques in the translation of CSIs in five selected stories from Muhammad Umar Memon’s book "The Greatest Urdu Stories Ever Told." Venuti’s theory of domestication serves as the study’s theoretical foundation. Ramière (2006) employs both methods along the foreignization and domestication spectrum. The spectrum is broken down into six techniques: borrowing, literal translation, glossing, omission, neutralization, and cultural substitution. The first three of these six processes are regarded as foreignized, while the last three are regarded as domesticated. CSIs are categorized for analysis purposes using Diaz-Chintas and Ramael’s (2014) taxonomy for CSIs. In order to thoroughly analyze the data, the researcher also employs a hybrid study type that combines qualitative and quantitative techniques. The degree of domesticaiton and that of foreignization, according to analysis of the stories, are 59% and 41% respectively. And this proves that the stories are more assimilated rather than alienated.